Learning Strategies in Speaking Skill Applied by A Student in Second Grade of SMK Pelita Nusantara Kediri - Nurhajati, Diani; Azizah, Alfianti (English Education:Journal of English Teaching and Research, 2016)
Most of the students get difficulties when they want to communicate to others. It is caused many factors including the limited students’ vocabularies, pronunciation, the idea that they are delivered, and knowledge of grammar. To increase the students’ speaking ability, they usually apply certain strategies in learning. This research aims to investigate what strategies and how they are applied to solve the difficulties in speaking and increasing the ability of speaking. The subject of research is a student in second grade of SMK Pelita Nusantara Kediri. She is the best student of second grade and she always gets the best ranking. The writer did some observations and interview to get the data. There are two kinds of learning strategies that applied; they are direct strategies and indirect strategies. Direct strategies are language learning strategies that directly involve the target language, and indirect strategies are language learning strategies that support and manage language learning without directly involving the target language. Direct strategies that are applied are memory strategies that reflect very simple principles such as arranging things in order, making association, and reviewing, cognitive strategies that most important strategies are practicing, and compensation strategies which intended to make up for an adequate repertoire of grammar and, especially, of vocabularies. In indirect strategies that are applied are metacognitive strategies which provide a way for learners to coordinate their own learning process, affective strategies that help to regulate emotions, motivations, and attitudes, and social strategies that can help all learners increase their ability to empathize by developing culture understanding and becoming aware of others’ thoughts and feelings. It can be found that the strategies mostly used were cognitive strategies and social strategies. Cognitive strategy used was practicing by repeating, recognizing and using formula and patterns, and practicing naturalistically. Social strategies used were asking questions and cooperating with others.